Authorea
DOI: 10.22541/au.158575923.31463773
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an essential binding site for local anesthetics in the ‘side pockets´ of Kv1 channels

Abstract: Background and Purpose: Local anesthetics block sodium and a variety of potassium channels. Although previous studies identified a residue in the pore signature sequence together with three residues in the S6 segment as a putative binding site, the precise molecular basis of Kv potassium channel inhibition by local anesthetics remained unknown. Kv crystal structures predict that some of these residues point away from the central cavity and face into a drug binding site called 'side pockets . Thus, the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The higher affinity of these blockers for TASK-1 channels suggests that TASK-1 could be an unrecognized molecular target of Kv1.5 blockers, effective in AF [11]. In the case of local anesthetics (LAs), it has been observed that bupivacaine and ropivacaine, which block Kv1.5 [12,[14][15][16][17], also act as blockers in TASK-1. In addition, LA lidocaine blockade has been reported on the TASK-1 channel [13,18] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The higher affinity of these blockers for TASK-1 channels suggests that TASK-1 could be an unrecognized molecular target of Kv1.5 blockers, effective in AF [11]. In the case of local anesthetics (LAs), it has been observed that bupivacaine and ropivacaine, which block Kv1.5 [12,[14][15][16][17], also act as blockers in TASK-1. In addition, LA lidocaine blockade has been reported on the TASK-1 channel [13,18] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%